Elevated Rho‐Kinase Activity as a Marker Indicating Atherosclerosis and Inflammation Burden in Polyvascular Disease Patients With Concomitant Coronary and Peripheral Arterial Disease. Issue 6 (28th March 2013) - Dong, Ming; Jiang, Xin; Liao, James K.; Yan, Bryan P.
Abstract Background Recent evidence suggests that Rho‐kinase (ROCK) plays an important role in the pathogenesis of atherosclerosis and a marker of atherosclerotic burden. Polyvascular disease with concomitant peripheral arterial disease (PAD) and coronary artery disease (CAD) is common and associated with a worse prognosis. The aim of this study was to evaluate ROCK activity as a marker of polyvascular disease. Hypothesis Methods We retrospectively analyzed patients undergoing coronary angiography at our institution between February 2009 and May 2009. Patients with only CAD (n = 40) defined by coronary artery stenosis of ≥50% by angiography, only PAD (n = 40) defined by an ankle brachial index (ABI) <0.9, and combined CAD/PAD (n = 40) were matched by age and sex to control patients (n = 40) without CAD or PAD. ROCK activity was determined by phosphorylation of the myosin binding subunit in leukocytes and then compared between each group. Multivariate analysis was used to determine independent predictors of polyvascular disease. Discriminative ability of elevated ROCK activity was assessed using receiver operator characteristics (ROC) curves. Results Patients (age 68 ± 12 years, 79% male) with CAD, PAD, and CAD/PAD had a mean ABI of 1.08, 0.62, and 0.65, respectively, compared to 1.08 in the control group. There was an incremental increase in ROCK activity in patients with CAD (4.61 ± 2.11), PAD (4.27 ± 1.39), and CAD/PAD (5.96 ± 1.94) compared to control (2.40 ± 0.43) (all P < 0.05). ROCK activity (odds ratio: 4.53, 95% confidence interval: 1.26‐6.30) was an independent predictor of polyvascular disease. The ROCK cutoff value of 4.85 had a sensitivity of 72.7% and a specificity of 65.7%, with an area under ROC curve of 0.71 for polyvascular disease. Conclusions Patients with concomitant peripheral and coronary arterial disease are associated with increased Rho‐kinase activity. Rho‐kinase activity may be a potential marker of atherosclerotic burden for patients with polyvascular disease.